STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA DAN EFISIENSI ORGANISASI - Asriani, Asriani; Hamriani, Selvi; Misran, Misran (IQRA : JURNAL MAGISTER PENDIDIKAN ISLAM, 2024)
Human resources are a very central element in any organization, whatever its form and purpose. Organizations were founded based on different visions for the benefit of society. Human resource development is a series of activities aimed at improving employee skills, knowledge, abilities and attitudes in order to improve individual and organizational performance. Human resource development also includes various strategies and techniques to optimize employee potential to better achieve company goals. The purpose of this article is to understand human resource development. Apart from that, the objectives and stages of human resource development will also be discussed. It is hoped that this article will provide a deeper understanding of human resource development.